A NEW VISION FOR EDUCATION IN QUALITY - Reinecke, Robert (The South African Journal of Industrial Engineering, 2011)
Excellence in manufacturing follows immediately from the complementaJy attributes of productivity and quality. Both have a cultural and technical component. A culture ofexcellence in both doijlg th ri2ht and doing the thing right is a